Water Quality Index of Sungai Tunggak : An Analytical Study - Nasly, Mohamed Ali; Hossain, Mohammed Amjed; Islam, Mir Sujaul (2013)
Water quality deterioration of Tunggak River is the impact of rapid industrialization at Gebeng, Malaysia. The aim of the study was to evaluate the water quality of the river using the application of WQI. To achieve the objectives 180 water samples were collected and comprehensive physicochemical analysis was done using APHA & HACH standard methods of analysis. The WQI was calculated using DOE-WQI based on the concentration of DO, BOD, COD, SS, pH and NH3-N. Results showed the sequence of monitoring stations 7<5<3<2<6<4<8<10<1<9 based on WQI value; where the first 7 (mid-stream) stations were categorized as class IV (highly polluted) and the last 3 were classified as class III (polluted). It was mainly because of low concentration of DO and high concentration of BOD, COD and NH3-N in the mid-stream due to the industrial activities. According to the INWQS, Malaysia water of the river cannot be used except irrigation.